Ppofessional risk industry factors = Професійні фактори ризику в умовах виробництва = Профессиональные факторы риска в условиях производства - T. M. Popova; O. G. Melnyk; I. Yu. Bagmut; A. I. Riabokon; A. V. Titkova (Kazimierz Wielki University, 2017)
Popova T. M., Melnyk O. G., Bagmut I. Yu., Riabokon A. I., Titkova A. V. Ppofessional risk industry factors = Професійні фактори ризику в умовах виробництва = Профессиональные факторы риска в условиях производства. Journal of Education, Health and Sport. 2016;6(11):511-519. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192143 http://ojs.ukw.edu.pl/index.php/johs/article/view/4032         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016.   UDK 613.6.027: 663.97.05   PROFESSIONAL RISK INDUSTRY FACTORS   T. M. Popova, *O. G. Melnyk, I. Yu. Bagmut, *A. I. Riabokon, A. V. Titkova   Kharkiv Medical Academy of Postgraduate Education; *Kharkiv National Medical University   Summary The hygienic estimation of the main workplace conditions at the tobacco production is presented in this article. The process of tobacco production is divided into two important stages: preparation of tobacco and the production of cigarettes. The first stage occurs in the tobacco department and second ones takes place in the cigarette department. The tobacco department workers are exposed to elevated concentration of tobacco dust 6,5 mg/m3 (maximum permissible concentration (MPC) 3,0 mg/m3),  noise level is 82-83 dBA that more maximum permissible limit (MPL 80 dBA) for 8 hours working period and adverse microclimate. During eight hours the cigarette department workers are exposed to high noise level 82-83 dBA, the same as previous stage, but concentration of tobacco dust is not higher than MPC. By results of the estimation of working conditions at the tobacco factory among the basic harmful and dangerous production factors are the tobacco dust, industrial noise, adverse microclimate, severity and intensity of work. Key words: occupational risk factors, tobacco dust, industrial noise.     ПРОФЕСІЙНІ ФАКТОРИ РИЗИКУ В УМОВАХ ВИРОБНИЦТВА   Т. М. Попова, *О. Г. Мельник, І. Ю. Багмут, *А. І. Рябоконь, А. В. Тіткова   Харківська медична академія післядипломної освіти; *Харківський національний медичний університет   Резюме У статті наведена гігієнічна характеристика умов праці робітників основних цехів виготовлення тютюнових виробів. Процес виробництва сигарет вміщує два важливих етапи: підготовки тютюну і власне виробництво цигарок та сигарет. Перший етап відбувається у тютюновому цеху, а другий - у цигарково-сигаретному. Визначено, що робітники тютюнового цеха працюють в умовах тривалого впливу підвищених концентрацій тютюнового пилу 6,5 мг/м3, що перевищує ГДК на 3,5 мг/м3, підвищеного рівня шуму - 82-83 дБА (вище за ГДР на 2-3дБА) та несприятливих мікрокліматичних умовах. Щодо цигарково-сигаретного цеху, то його працівники, протягом 8 годин, піддаються впливу тютюнового пилу (концентрація у межах ГДК), дії підвищеного рівня шуму (вище за ГДР на 2-3дБА). За результатами оцінки умов праці на тютюновій фабриці серед основних шкідливих і небезпечних виробничих факторів виробництва є тютюновий пил, промисловий шум, несприятливий мікроклімат, важкість і інтенсивність праці. Ключові слова: професійні фактори ризику, тютюновий пил, виробничий шум.   ПРОФЕССИОНАЛЬНЫЕ ФАКТОРЫ РИСКА В УСЛОВИЯХ ПРОИЗВОДСТВА   Т. М. Попова, *О. Г. Мельник, И. Ю. Багмут, *А. И. Рябоконь, А. В. Титкова   Харковская медицинская академия последипломного образования; *Харковский национальный медицинский университет   Резюме В статье дана гигиеническая характеристика рабочих мест основных цехов производства табачных изделий. Процесс производства сигарет включает два важных этапа: подготовка табака и собственное производство папирос и сигарет. Первый этап происходит в табачном цехе, а второй - в папиросо-сигаретном. Установлено, что рабочие табачного цеха работают в условиях длительного воздействия повышенных концентраций табачной пыли 6,5 мг/м3, которая превышает ПДК в 3,5мг/м3, повышенного уровня шума - 82-83 дБА (ПДУ 80 дБА), неблагоприятных микроклиматических условий. В папиросо-сигаретном цехе в течение трудового дня на рабочих воздействует табачная пыль (концентрация в пределах ПДК), производственный шум 82-83 дБА (ПДУ 80 дБА). По результатам оценки условий труда на табачной фабрике среди основных вредных и опасных производственных факторов является табачная пыль, промышленный шум, неблагоприятный микроклимат, тяжесть и интенсивность труда. Ключевые слова: профессиональные факторы риска, табачная пыль, производственный шум.